(untitled) (Journal of Asian Development Studies, 2025)
Drawing on the Upper Echelon Theory (UET) and the Ability-Motivation-Opportunity (AMO) framework, the purpose of this study is to examine the impact of six green HRM practices, such as green recruitment and selection (GRS), green reward and compensation (GRC), employees’ green empowerment and participation (EGEP), green organizational culture (GOC), green performance management system (GPMS), green training and development (GTD) on environmental performance of organizations (EPO) in textile industry of Pakistan. The study also analyses the moderating role of green internal environmental orientation (GIEO) in the relationships between GHRM practices and EPO. The data were collected from 445 employees, working at the managerial level of 20 green-certified large textile Mills located in Multan and Faisalabad divisions of Pakistan through a questionnaire survey. PLS-SEM structural modelling techniques were employed to predict these relationships. According to findings, all six green HRM practices have positive and significant impacts on the environmental performance of organizations. However, the impact of green internal environmental orientation (GIEO), which is proxied to top management commitment to environmental sustainability, has an insignificant impact on this relationship. The study predicts that green HRM practices are more effective tools than green internal environmental orientation (GIEO) to enhance the environmental performance of organizations.